Ocena skuteczności różnych form elektroterapii w leczeniu objawów zmian zwyrodnieniowych stawów kolanowych = Evaluating the effectiveness of different forms of electotherapy in the treatment the symptoms of knee osteoarthritis - Mariusz Baumgart; Agnieszka Kapsa; Magdalena Weber-Rajek; Agnieszka Radzimińska; Sebastian Szyper; Michał Szpinda; Walery Zukow (Kazimierz Wielki University, 2016)
Baumgart Mariusz, Kapsa Agnieszka, Weber-Rajek Magdalena, Radzimińska Agnieszka, Szyper Sebastian, Szpinda Michał, Zukow Walery. Ocena skuteczności różnych form elektroterapii w leczeniu objawów zmian zwyrodnieniowych stawów kolanowych = Evaluating the effectiveness of different forms of electotherapy in the treatment the symptoms of knee osteoarthritis. Journal of Education, Health and Sport. 2016;6(5):131-138. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.51333 http://ojs.ukw.edu.pl/index.php/johs/article/view/3516     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.04.2016. Revised 29.04.2016. Accepted: 11.05.2016.   Ocena skuteczności różnych form elektroterapii w leczeniu objawów zmian zwyrodnieniowych stawów kolanowych Evaluating the effectiveness of different forms of electotherapy in the treatment the symptoms of knee osteoarthritis   Mariusz Baumgart1, Agnieszka Kapsa2, Magdalena Weber-Rajek3, Agnieszka Radzimińska3, Sebastian Szyper4, Michał Szpinda1, Walery Zukow5   • Katedra i Zakład Anatomii Prawidłowej, Collegium Medicum w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu, Polska • Bydgoska Szkoła Wyższa w Bydgoszczy, Polska • Katedra Fizjoterapii, Zakład Podstaw Fizjoterapii, Collegium Medicum w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu, Polska • Katedra Higieny, Epidemiologii i Ergonomii, Collegium Medicum w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu, Polska • Uniwersytet Kazimierza Wielkiego, Bydgoszcz, Polska   Słowa kluczowe: choroba zwyrodnieniowa stawów kolanowych, elektroterapia.   Keywords: knee osteoarthritis, electotherapy.   Streszczenie Integralną metodą leczenia choroby zwyrodnieniowej jest fizjoterapia. Przedmiotem niniejszych badań były dwie metody elektroterapeutyczne: prądy interferencyjne (IFC) i przezskórna stymulacja nerwów (TENS). Analiza uzyskanych wyników badań wykazała, iż elektrostymulacja prądami interferencyjnymi i TENS jest skuteczną metodą w łagodzeniu objawów zmian zwyrodnieniowych stawów kolanowych. Porównując wyniki między badanymi grupami nie wykazano różnic istotnych statystycznie.   Summary Physical therapy is an integral method of treatment of osteoarthritis. The subject of this study, was two methods of electrotherapy: interferential current (IFC) and transcuteneus electical nerve stimulation (TENS).  Analysis of the results showed that IFC and TENS is an effectivnes method in relieving symptoms of osteoarthritis of the knee joint. Comparing the results between the two groups showed no statistically significant differences.